The organization, weaknesses, and challenges of the control of thalidomide in Brazil: A review - Jesus, Soraya Machado de; Santana, Rafael Santos; Leite, Silvana Nair (PLOS Neglected Tropical Diseases, 2020)
The drug thalidomide has resurged in the world market under restrictive conditions for marketing and use. In Brazil, there are still cases of pregnant women using thalidomide even after the implementation of laws that regulate the control of use (Law No. 10.651/2003 and Collegiate Board Resolution No. 11/2011). The objective of this study was to discuss the control of thalidomide use in Brazil, based on a scoping review of the scientific literature, documents, and data from the Ministry of Health. A total of 51 studies and documents related to the following subthemes were selected: (1) organization of access and use of thalidomide in the health system; (2) epidemiological and population characteristics of people affected by leprosy; and (3) occurrence of pregnancy and cases of embryopathy with the use of thalidomide. The results showed that Brazil has no unified information database about thalidomide patients. Furthermore, there is inconsistency in the accreditation of public health centers that dispense this medicine, in a country that has a high consumption of thalidomide in the Unified Health System. A large part of this amount of dispensed medicine is intended for the treatment of erythema nodosum leprosum, mainly in the North, Northeast, and Central-West regions of the country, which are endemic for leprosy. This disease is the only one among the clinical indications of the medicine approved in Brazil that does not have a Clinical Protocol and Therapeutic Guidelines. The control of thalidomide use in Brazil presents historical regulatory failures. These are currently linked to the organization and structure of primary healthcare in the country, as well as to the lack of leadership of the Ministry of Health and National Health Surveillance Agency when it comes to managing the process of control of this use.